Geographic characteristics and environmental variables determine the diversities and assembly of the algal communities in interconnected river-lake system. (15th April 2023) - Wu, Shanghua; Dong, Yuzhu; Stoeck, Thorsten; Wang, Shijie; Fan, Haonan; Wang, Yaxin; Zhuang, Xuliang
Highlights: Assembly mechanisms of algae in complex interconnected river-lake ecosystems. N:P ratio and Cu concentration determined the non-linear response of benthic algae. Disperse of algae from upstream rivers determined the planktonic algae. Abstract: Algal blooms in lakes are a major hazard worldwide. Although various geographical and environmental patterns affect algal communities during river-lake transit, a thorough understanding of what patterns shape the algal communities is still rarely researched, particularly in complex interconnected river-lake systems. In this study, focusing on the most typical interconnected river-lake system in China, the Dongting Lake, we collected paired water and sediment samples in summer, when algal biomass and growth rate are at high levels. Based on 23S rRNA gene sequencing, we investigated the heterogeneity and the differences in assembly mechanisms of planktonic and benthic algae in Dongting Lake. Planktonic algae contained more Cyanobacteria and Cryptophyta, while sediment harbored higher proportions of Bacillariophyta and Chlorophyta. For planktonic algae, stochastic dispersal dominated the assembly of the communities. Upstream rivers and confluences were important sources of planktonic algae in lakes. Meanwhile, for benthic algae, deterministic environmental filtering shaped the communities, and the proportion of benthic algae exploded with increasing N:P ratio and Cu concentration until reaching thresholds of 1.5 and 0.013 g/kg respectively, and then started falling, showing non-linear responses. This study revealed the variability of different aspects of algal communities in different habitats, traced the main sources of planktonic algae, and identified the thresholds for benthic algal shifts in response to environmental filters. Hence, upstream and downstream monitoring as well as thresholds of environmental factors should be considered in further aquatic ecological monitoring or regulatory programs of harmful algal blooms in these complex systems. Graphic abstract: Image, graphical abstract